2012
DOI: 10.1073/pnas.1114748109
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic basis for calcium regulation of sodium channels

Abstract: Voltage-gated sodium channels underlie the rapid regenerative upstroke of action potentials and are modulated by cytoplasmic calcium ions through a poorly understood mechanism. We describe the 1.35 Å crystal structure of Ca 2+ -bound calmodulin (Ca 2+ /CaM) in complex with the inactivation gate (DIII-IV linker) of the cardiac sodium channel (Na V 1.5). The complex harbors the positions of five disease mutations involved with long Q-T type 3 and Brugada syndromes. In conjunction with isothermal titration calori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
140
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(157 citation statements)
references
References 44 publications
(72 reference statements)
11
140
6
Order By: Relevance
“…Our model shows CNGC12 mediating Ca 2+ influx directly; however, we cannot exclude the possibility that CNGC12 signaling triggers Ca 2+ current(s) mediated by other channel(s). Our model includes speculative features that are consistent with our results to date but which require further experimental investigation and some of which bear clear similarities to various animal channels, such as CaM-mediated bridging of inter-and intrasubunit interactions and dynamic movement of CaM between multiple CaMBDs (Fallon et al, 2009;Liu and Vogel, 2012;Sarhan et al, 2012;Morales et al, 2013;Ben Johny et al, 2013;Shao et al, 2014). Interestingly, such CaM regulatory features are widely distributed among various animal voltage-or Ca 2+ -gated cation channels for which there are no clear homologs in plants (Edel and Kudla, 2015).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Our model shows CNGC12 mediating Ca 2+ influx directly; however, we cannot exclude the possibility that CNGC12 signaling triggers Ca 2+ current(s) mediated by other channel(s). Our model includes speculative features that are consistent with our results to date but which require further experimental investigation and some of which bear clear similarities to various animal channels, such as CaM-mediated bridging of inter-and intrasubunit interactions and dynamic movement of CaM between multiple CaMBDs (Fallon et al, 2009;Liu and Vogel, 2012;Sarhan et al, 2012;Morales et al, 2013;Ben Johny et al, 2013;Shao et al, 2014). Interestingly, such CaM regulatory features are widely distributed among various animal voltage-or Ca 2+ -gated cation channels for which there are no clear homologs in plants (Edel and Kudla, 2015).…”
Section: Discussionsupporting
confidence: 68%
“…association between CaM and IQ motifs is a widespread phenomenon among animal cation channels (Kovalevskaya et al, 2013) but had not previously been confirmed in plants. Our data suggest that CaM may be responsible for Ca 2+ -dependent intraand/or intersubunit interactions, another feature thought to be specific to animal cation channels (Fallon et al, 2009;Liu and Vogel, 2012;Sarhan et al, 2012). This is an interesting avenue for investigation, given that homo-or heterotetramers are hypothesized to comprise functional CNGCs in vivo (Kaplan et al, 2007;Zelman et al, 2012), though to date we have only minimal data regarding how different plant CNGC subunits associate .…”
Section: Discussionmentioning
confidence: 99%
“…Secondary structures were calculated using Stride (Frishman & Argos, 1995). Solvent accessibility and interface burial were calculated using the GETAREA tool (Fraczkiewicz & Braun, 1998) on the following PDB entries: for UBE2I: 3UIP (Gareau et al , 2012); 4W5V (Boucher et al unpublished); 3KYD (Olsen et al , 2010); 2UYZ (Knipscheer et al , 2007); 4Y1L (Alontaga et al , 2015); for SUMO1: 2G4D (Xu et al , 2006); 2IO2 (Reverter & Lima, 2006); 3KYD (Olsen et al , 2010); 3UIP (Gareau et al , 2012); 2ASQ (Song et al , 2005); 4WJO (Cappadocia et al , 2015); 4WJQ (Cappadocia et al , 2015); 1WYW (Baba et al , 2005); for calmodulin: 3G43 (Fallon  et al , 2009); 4DJC (Sarhan et al , 2012); and for TPK1: 3S4Y (Baker et al , 2001). …”
Section: Methodsmentioning
confidence: 99%
“…Two helices connected by CaM have been observed or inferred in several instances (Schumacher et al, 2001;Yap et al, 2003;Houdusse et al, 2006;Wang et al, 2008;Fallon et al, 2009;Zhang et al, 2012;Sarhan et al, 2012), although the functional relevance of this engulfing arrangement has on occasion been brought into question (Kim et al, 2010). An organization of this kind is crucial for Ca 2+ -CaM mediated gating of small conductance Ca 2+ -activated K + channels (Schumacher et al, 2001).…”
Section: Discussionmentioning
confidence: 99%